Effects of language proficiency and communication on procedural justice in an international joint venture. (2nd July 2020) - Makowski-Komura, Lara; Bebenroth, Ralf; Malik, Ashish
ABSTRACT: In cross-border partnerships, several language strategies have been identified for better outcomes between interacting employees of two contracting parties: adopting a common corporate language (CCL), increasing the frequency of communication and employing translation services. This study empirically examines the factors influencing procedural justice in the context of a Japanese-European international joint venture (IJV). The findings from our research suggest that perceived common corporate language differences (CC-LADs) and frequency of communication both have an influence on procedural justice in the decision-making process of key employees. While a higher self-perceived CC-LAD led to a negative, higher communication frequency led to a positive perception of justice. The paper also found a moderation effect of frequency on perceived CC-LADs, suggesting that employees with higher CC-LAD see decision-making processes as fairer when communication occurs more frequently. Direct effects are even applicable to the small group of employees who perceive their own CCL ability higher than that of their counterparts whereas a moderation effect is applicable for the employees who perceive their CCL ability as lower than their counterparts.